Taking a Shortcut: Direct Power-to-X Conversion - Mi, Zetian; Sick, Volker (Frontiers in Energy Research, 2020)
Power-to-X technologies provide avenues to help de-fossilize a range of large-scale technologies in the mobility, manufacturing, chemical, as well as energy delivery industries. This relates to energy carriers such as hydrogen and hydrocarbons as well as availability of feedstock materials, such as methanol. Technologies for solar and wind-generated electricity and subsequent electrochemical processing are available and are further developed for efficiency and yields. An alternative pathway can be pursued by fully integrating the electricity generation and chemical conversion into one device, thereby reducing technical complexity and removing inefficiencies due to multi-step cascading of processes. In this perspective article, we provide an overview on the recent developments and prospects of artificial photosynthesis, i.e., the chemical transformation of sunlight, water, and carbon dioxide into high-energy-rich fuels. Primary discussions will be focused on the recent development of scalable artificial photosynthesis technology using common semiconductors, e.g., silicon and gallium nitride, for solar fuel production. Technology advances for both hydrogen production from solar water splitting and liquid fuel generation from CO2 reduction will be discussed. The basic operating principles and potential integration with existing and emerging energy infrastructures will be analyzed. The challenges, future prospects of achieving sustainable, large scale applications will also be presented.